Poly(acrylic acid) Enabling the Synthesis of Highly Uniform Silica Nanoparticles of sub‐100 nm. Issue 3 (18th February 2022) - Hu, Feng; Rasamani, Kowsalya Devi; Abeyweera, Sasitha C.; Zhang, Dongtang; Sun, Yugang
Abstract: Robust synthesis of small colloidal silica (SiO2 ) nanoparticles with narrow size distributions (<5%) is challenging because the possible involvement of continuous nucleation and growth of SiO2 in the widely used Stöber process usually results in silica nanoparticles with large sizes and broad size distributions. Promoting heterogeneous nucleation and growth of silica is promising to tackle the challenges by in‐situ forming transient colloidal seeds that provide nucleation surfaces for silica condensate. In this work, poly(acrylic acid) (PAA) is introduced to the Stöber synthesis solutions, which are usually composed of ethanol (containing a trace amount of water), tetraethyl orthosilicate (TEOS), and ammonia, to mediate the nucleation of TEOS hydrolysates and growth of SiO2 nanoparticles. PAA reacts with ammonia to form soft PAA‐NH3 complex colloids that serve as transient seeds to facilitate heterogeneous nucleation and growth of SiO2 nanoparticles after adding TEOS to the synthesis solution. The number of PAA‐NH3 complex colloidal particles, which strongly depends on the molar ratio of PAA and ammonia, determines the number of the resulting SiO2 nanoparticles and thus the size of the SiO2 nanoparticles correspondingly according to the supply of TEOS. Highly uniform SiO2 nanoparticles with finely tuned diameters in the sub‐100 region have been successfully synthesized, and the synthesis protocol is feasible to be scaled up while maintaining the high quality of SiO2 nanoparticles. Abstract : The acid‐base reaction between poly(acrylic acid) and ammonia forms a complex to agglomerate the polymer molecules into colloids in ethanol. The polymer colloidal nanoparticles serve as transient seeds to mediate heterogeneous nucleation and growth of highly uniform silica nanoparticles with precisely controlled sizes below 100 nm. The synthesis protocol is feasible to be scaled up for mass production.